Topical antibiotics for acute rhinosinusitis in children - E. P. Karpova (Медицинский совет, 2020)
In this article, the authors provide an overview of existing data on the use of topical antibacterial drugs in acute rhinosinusitis in children. General information on the etiology of acute rhinosinusitis is given. Indications for systemic and topical antibiotic therapy in acute rhinosinusitis are noted, indicated in Russian and international consensus documents. The advantages of using the combined preparation of thiamphenicol and N-acetylcysteine in acute rhinosinusitis in children and adults are considered separately. It is concluded that the topical antibacterial therapy of acute rhinosinusitis, despite all its advantages, is not an equivalent substitute for systemic antibacterial therapy in the treatment of severe and, especially, complicated forms of acute rhinosinusitis. The practitioner should be guided by the indications for systemic and topical antibacterial therapy adopted in Russian consensus documents. If there are indications for systemic antibiotic therapy, local remedies are only ancillary treatment, the action of which is aimed at enhancing the effect of systemic antibiotics. In the case of monotherapy with local drugs containing antibacterial components, it is mandatory to re-evaluate the patient’s condition and the dynamics of the symptoms of the disease for 2–3 days of treatment, and in the absence of positive changes, reconsider the need for systemic antibacterial therapy. More promising is the use of combined drugs that, in addition to affecting the causative agent of the disease, achieve anti-inflammatory, decongestion or mucolytic effects. It is convenient and rational to use nasal sprays, however, in order to improve the delivery of the active substance to the site of inflammation in acute rhinosinusitis, the use of nebulizer is justified.